Does Isomorphism Legitimate? - Deephouse, David L. (Academy of Management Journal, 1996)
This study tests a central proposition of institutional theory, that organizational isomorphism increases organizational legitimacy. Results show that isomorphism in the strategies of commercial banks is related to legitimacy conferred by bank regulators and the media, even in the presence of organizational age, size, and performance.